Smart home system using internet of things: design, implementation and sample codes - Yaldi, Intan Rahmithul Husna; Gunawan, Teddy Surya; Kartiwi, Mira (LAP Lambert Academic Publishing, 2018)
Smart home control system (SHCS) can be integrated into an existing home appliances to reduce the need for human intervention, increase security and energy efficiency. It is still an open research due to difficulties such as network distance, signal interference, user friendliness, high cost, and high power consumption. This book reviews various topics on smart home technologies, including control system, smart home network, smart home appliance and sensor technologies for smart home. A smart home system using internet of things was proposed using internet of things (IoT) and four types of sensors, including PIR, temperature, ultrasonic, and smoke gas sensor for automatic environmental control and intrusion detection. Hardware, software, and test field design will be discussed. The performance of the prototype of smart home system will be evaluated. First, experiments on various sensors will be conducted. Next, the communication channel using wireless and Ethernet modules will be discussed. Moreover, the overall SHCS will be evaluated in terms of hardware and software performance with additional solar charger to improve power efficiency.